To factor the polynomial \( f(x) = x^3 - 3x^2 - 10x + 24 \) using the Factor Theorem, we first confirm that \( x = 2 \) is indeed a zero. Then we can divide \( f(x) \) by \( (x - 2) \) to find the other factors.
Step 1: Synthetic Division
Using synthetic division with \( x = 2 \):
2 | 1 -3 -10 24
| 2 -2 -24
---------------------------
1 -1 -12 0
The result is \( x^2 - x - 12 \), and since there's a zero remainder, we have:
\[ f(x) = (x - 2)(x^2 - x - 12) \]
Step 2: Factor the Quadratic
Next, we need to factor \( x^2 - x - 12 \). We look for two numbers that multiply to \(-12\) and add to \(-1\). The numbers \(-4\) and \(3\) fit this requirement:
\[ x^2 - x - 12 = (x - 4)(x + 3) \]
Step 3: Combine All Factors
Now we can write \( f(x) \) as:
\[ f(x) = (x - 2)(x - 4)(x + 3) \]
Final Answer
Thus, the factored form of the polynomial \( f(x) \) into linear factors is:
\[ f(x) = (x - 2)(x + 3)(x - 4) \]
Among the provided options, the correct response is:
f(x) = (x - 2)(x + 3)(x - 4).